Risk factors for non-adherence to oral anticoagulant therapy and the potential of their modification in patients with atrial fibrillation: a narrative literature review - I. M. Felikov; V. V. Kashtalap (Российский кардиологический журнал)
Medication adherence is a key factor of effective stroke prevention in patients with atrial fibrillation receiving oral anticoagulant therapy. At the same time, patient compliance can significantly decrease over time, which leads to an increased thromboembolism risk. A number of studies have shown that a large number of patients receiving anticoagulant therapy are insufficiently adherent to therapy (according to various sources, from 30 to 50% of patients do not comply with the prescribed treatment regimen or interrupt therapy).Independent risk factors for non-compliance include younger age, old age, prior stroke, male sex, multimorbidity, polypharmacy. The risk of decreased compliance with double drug intake compared to single one is noted separately.The review aim is to study the risk factors for non-adherence to oral anticoagulants in patients with atrial fibrillation and possible measures for its prevention.